Rational design of one-dimensional vanadium(v) oxide nanocrystals: an insight into the physico-chemical parameters controlling the crystal structure, morphology and size of particles. Issue 36 (28th September 2015) - Steunou, Nathalie; Livage, Jacques
<x xml:space="preserve">Abstract</x> This highlight deals with the recent advances on the synthesis in aqueous solution of one-dimensional vanadium(v) oxide nanocrystals.